2007
DOI: 10.1016/j.bmc.2006.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the 5-phosphono-pent-2-en-1-yl nucleosides: A new class of antiviral acyclic nucleoside phosphonates

Abstract: A new class of acyclic nucleoside phosphonates, the 5-phosphonopent-2-en-1-yl nucleosides and their hexadecyloxypropyl esters were synthesized from butyn-1-ol. Only the hexadecyloxypropyl esters showed antiviral activity against herpes simplex virus type 1, in vitro. Hexadecyloxypropyl 1-(5-phosphono-pent-2-en-1-yl)thymine was the most active and selective compound among the synthesized nucleotides with an EC 50 value of 0.90 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Choo et al reported the preparation of the alkoxyalkyl cis- 5-phosphono-pent-2-en-1-yl nucleoside prodrug 299 . 123 Uracil diethyl phosphonate derivative 297 was first synthesized by Mitsunobu coupling between N 3 -benzoylated uracil and ( Z )-diethyl (5-hydroxypent-3-en-1-yl)phosphonate followed by debenzoylation with ammonia in methanol. Triisopropylphenylsulfonylation and subsequent aminolysis converted the uracil diethylphosphonate 297 into its corresponding cytosine derivative 298 in 75% yield.…”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%
“…Choo et al reported the preparation of the alkoxyalkyl cis- 5-phosphono-pent-2-en-1-yl nucleoside prodrug 299 . 123 Uracil diethyl phosphonate derivative 297 was first synthesized by Mitsunobu coupling between N 3 -benzoylated uracil and ( Z )-diethyl (5-hydroxypent-3-en-1-yl)phosphonate followed by debenzoylation with ammonia in methanol. Triisopropylphenylsulfonylation and subsequent aminolysis converted the uracil diethylphosphonate 297 into its corresponding cytosine derivative 298 in 75% yield.…”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%
“…A new class of acyclic nucleoside phosphonate was recently reported having a 5-phosphono-pent-2-en-1-yl acyclic side chain loosely based on the structure of d4T (Choo et al 2007a). Unmodified acyclic nucleoside phosphonates of this class are inactive against HSV-1.…”
Section: Application Of the Same Strategy To Other Acyclic Nucleosmentioning
confidence: 99%
“…Unmodified acyclic nucleoside phosphonates of this class are inactive against HSV-1. However, when esterified with HDP, the HDP-PPen-T compound exhibits antiviral activity against HSV-1 in vitro (Choo et al, 2007a). None of the unmodified PPen nucleosides are active against HIV or HBV (Choo et al, 2007b).…”
Section: Application Of the Same Strategy To Other Acyclic Nucleosmentioning
confidence: 99%
See 1 more Smart Citation
“…HSV-1 is responsible for the lesions at orofacial sites that are commonly known as cold sores. HSV-2 is responsible for mucocutaneous genital infections [3]. Much research has been focused on HSV-1 and HSV-2 as these viruses have a high incidence rate (1.6 million new cases of HSV-2 predicted per year in the United States) and prevalence [50-95% (HSV-1) and 6-50% (HSV-2)] [4].…”
Section: Introductionmentioning
confidence: 99%